Age factor and COVID-19 potential ethical and unethical issues - Santiago Herrero (Indonesian Nutrition Association, 2020)
The presentation of ethical guidelines by various scientific societies during the scenario of the COVID-19 pandemic in Spain is surprising when evidencing proposals for treatment and support due to